The involvement of NETs in ANCA-associated vasculitis - Shiratori-Aso, Satoka; Nakazawa, Daigo (Frontiers in Immunology, 2023)
Anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV) is a serious autoimmune disease that is characterized by vascular necrosis. The pathogenesis of AAV includes ANCA-mediated neutrophil activation, subsequent release of inflammatory cytokines and reactive oxygen species (ROS), and formation of neutrophil extracellular traps (NETs). Excessive NETs could participate not only in ANCA-mediated vascular injury but also in the production of ANCAs per se as autoantigens. Thus, a vicious cycle of NET formation and ANCA production is critical for AAV pathogenesis. Elucidating the molecular signaling pathways in aberrant neutrophil activation and NETs clearance systems will allow specific therapeutics to regulate these pathways. Currently, standard therapy with high doses of glucocorticoids and immunosuppressants has improved outcomes in patients with AAV. However, AAV frequently develops in elderly people, and adverse effects such as severe infections in the standard regimens might contribute to the mortality. Mechanistically, cytokines or complement factors activate and prime neutrophils for ANCA-binding; thus, C5a receptor blocker has garnered attention as potential replacement for glucocorticoids in clinical settings. Recent studies have demonstrated that receptor-interacting protein kinases (RIPK3) and cyclophilin D (CypD), which regulate cell necrosis, may be involved in ANCA-induced NETs formation. Meanwhile, targeting NETs clearance, including the addition of deoxyribonuclease I (DNase I) and macrophage engulfment, may improve vasculitis. In this review, we focus on the pathogenesis of NETs and discuss potential targeted therapies for AAV based on recent experimental evidence.